Tensile actuation response of additively manufactured nickel-titanium shape memory alloys. (15th March 2018) - Sam, J.; Franco, B.; Ma, J.; Karaman, I.; Elwany, A.; Mabe, J.H.
Abstract: In the present work, we characterize the tensile shape memory actuation behavior of NiTi shape memory alloys (SMAs) fabricated using laser powder bed fusion (L-PBF) additive manufacturing process. The samples were fabricated using two different sets of processing parameters. While reversible tensile shape memory behavior was observed in both cases, the samples fabricated with a shorter hatch spacing exhibited higher transformation temperatures, lower actuation strain, and lower irrecoverable strain compared to the samples fabricated with wider hatch spacing. The actuation strain and ductility of the L-PBF samples were lower than that of the conventionally manufactured NiTi SMA samples. Graphical abstract: Changes in powder bed additive manufacturing process parameters (AM120 and AM35) notably change the martensitic transformation temperatures, tensile actuation response, actuation strain levels, and the sample-to-sample variation in shape memory characteristics as compared to the conventionally manufactured NiTi SMAs, providing an opportunity to manipulate the properties by controlling the process parameters. Image 1